The Combination of Polyhexamethylene Biguanide and Cadexomer Iodine in Healing Chronic Venous Leg Ulcers: A Case Report - Asmat Burhan; Septian Mixrova Sebayang (Viva Medika, 2022)
Chronic Venous Leg Ulcers (CVLUs) are vascular diseases and require complex wound care from a patient, wound, health personnel and dressing factors. Cadexomer Iodine (CI) and Polyhexamethylene Biguanide (PHMB) are antimicrobial and broad-spectrum wound washing fluids. The uncontrolled infection will complicate wound healing due to bacteria or plankton from the biofilm stage to infection, which causes a long healing time. Purpose: to determine the effectiveness of the combination of Polyhexamethylene biguanide and Cadexomer Iodine on venous leg ulcer wound healing. Methods: This study is a case study using CVLUs as a sample, with pre-test and post-test designs, patients with CVLUs received topical antimicrobial CI and PHMB interventions on wounds for 7 weeks. The sample in this study used one sample with a pre-post treatment design for seven days.. The instrument uses the Bates Jensen Wound Assessment Tool. Results: The combination of CI and PHMB was shown to improve the healing of CVLUs by controlling bacterial infection in wounds. In the 2nd week, the wound was 26cm x 15cm, the slough was reduced, and the red base wound increased. In the 3rd week, the wound was stage 4, and the granulation increase was 75%. In the 7th treatment, the wound size scale increased 7cmx4cm, the wound became stage 2, and a significant increase in epithelialization was 75%. Conclusion: The combination of PHMB and CI has been shown to control infection at the biofilm stage to critical colonization, reduce odour and significantly control infection, and increase granulation and epithelialization in CVLUs